2005
DOI: 10.1128/cdli.12.6.793-796.2005
|View full text |Cite
|
Sign up to set email alerts
|

Opsonization Effects onMycobacterium aviumsubsp.paratuberculosis-Macrophage Interactions

Abstract: High antibody titers in ruminants infected with Mycobacterium avium subsp. paratuberculosis correlates with disease progression. Effects of humoral responses during mycobacterial infection are not completely understood. This study suggests that activation status may be an important factor in determining macrophage ability to limit proliferation of opsonized M. avium subsp. paratuberculosis.Generally, the humoral response present during mycobacterial infections has been considered nonprotective; however, the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…can be ingested in the presence or absence of serum and it has been suggested that different entry pathways could affect bacilli survival into the macrophages [13,39]. Besides, other authors described that complete immune sera and normal bovine sera were similar in the ability to promote macrophage uptake of Map in vitro [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…can be ingested in the presence or absence of serum and it has been suggested that different entry pathways could affect bacilli survival into the macrophages [13,39]. Besides, other authors described that complete immune sera and normal bovine sera were similar in the ability to promote macrophage uptake of Map in vitro [19].…”
Section: Discussionmentioning
confidence: 99%
“…Maps were stained with fluorescein isothiocyanate (FITC, Sigma Chemical Co.) as described previously [19]. Briefly, 4 × 10 7 broth-grown bacteria were suspended in carbonate buffer (0.001% FITC in a 0.2 M Na 2 CO 3 -NaHCO 3 , 150 mM NaCl buffer) pH 9.2 for 30 min.…”
Section: Association Experiments Between Macrophages and Mapmentioning
confidence: 99%
“…At later stages of the infection animals with multi-bacillary lesions express predominantly a Th2-type immune response that is measured by the presence of MAP-specific IgG1 antibodies, production of which is driven by IL-4 or IL-10 producing CD4 T cells [18][20]. Although high levels of MAP-specific antibodies are detected in animals in late stages of the disease, these antibodies do not appear to be protective and may even be detrimental by increasing uptake of extracellular bacteria by macrophages [24]. Thus, experimental infections of sheep with MAP suggest a switch from dominance of the MAP-specific Th1 immune response in the early stages of the disease to a predominantly Th2 response at later stages of the disease (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…We next determined if these differences were attributable to variation in phagocytosis by measuring attachment/uptake of FITC labeled M. avium subsp. paratuberculosis by flow cytometry as previously described [5]. The level of attachment and uptake of M. avium subsp.…”
Section: Resultsmentioning
confidence: 99%